Nutritional and health aspects of food of Eastern Europe - Bogueva, Diana (Elsevier traditional and ethnic food series., 2022)
Nutritional and Health Aspects of Food in Eastern Europe provides an analysis of traditional and ethnic foods from Eastern Europe, including selections from Russia, Belarus, Ukraine, Estonia, Latvia and Lithuania. The book addresses history of use, origin, composition and preparation, ingredient origin, nutritional aspects, and the effects on health for various foods and food products in each of these countries. In addition, it presents both local and international regulations, while also providing suggestions on how to harmonize these regulations to promote global availability of these foods.